(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
This paper uses the input-output table data in 2012 of Canton, China, using CGE model to examine the effects of different population sizes on energy production, energy consumption and actual energy use in the same external conditions. The results show that the expansion of population size significantly drives up the amount of energy consumption. But the impacts of population growth on energy production and real energy prices are nonsignificant